2021
DOI: 10.1038/s41893-021-00756-w
|View full text |Cite
|
Sign up to set email alerts
|

Personal carbon allowances revisited

Abstract: Here we discuss how personal carbon allowances (PCAs) could play a role in achieving ambitious climate mitigation targets. We argue that recent advances in AI for sustainable development, together with the need for a low-carbon recovery from the COVID-19 crisis, open a new window of opportunity for PCAs. Furthermore, we present design principles based on the Sustainable Development Goals for the future adoption of PCAs. We conclude that PCAs could be trialled in selected climate-conscious technologically advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Those who are less pessimistic about the future climate are likely to be more concerned about the socio-political impact of surveillance. Perhaps the real debate is on how to balance, or even resolve, the tension between the urgency of climate action and concerns, such as privacy protection and liberty, and ensuring public participation in the decision-making process [73]. Transitioning away from carbon-intensive growth is urgently needed, but it is also important to do so in a just and socially acceptable manner [74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who are less pessimistic about the future climate are likely to be more concerned about the socio-political impact of surveillance. Perhaps the real debate is on how to balance, or even resolve, the tension between the urgency of climate action and concerns, such as privacy protection and liberty, and ensuring public participation in the decision-making process [73]. Transitioning away from carbon-intensive growth is urgently needed, but it is also important to do so in a just and socially acceptable manner [74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surveillance technologies developed to fight COVID-19, especially contact tracing, can provide useful information on how to estimate emissions by tracking movement history. Indirect emissions from food and other consumption can also be estimated using mobile apps to capture personal travel history, dietary behaviors, and purchasing habits, which can then be used to estimate carbon emissions [73]. Therefore, surveillance technologies for PCA are developing rapidly.…”
Section: Carbon Rationing: Individualsmentioning
confidence: 99%
“…Including carbon calculators with personalized feedback in high school science lessons about climate change would be an effective next step to help address the shortcomings in current curricula where high-impact actions are often ignored (9). Governments could also use this tool as part of a national climate plan to inform citizens about personal mitigation actions while simultaneously soliciting input about the necessary infrastructure and policies to support these changes (65). Although carbon calculators do not present a panacea for climate change, they could empower individuals in the immediate future to reduce their personal emissions and help reach sustainability goals.…”
Section: Discussionmentioning
confidence: 99%
“…In a PCA scheme, individuals would initially be allotted a free [3], and a limited number of allowances for emitting emissions which would later be surrendered when purchasing energy for travelling or domestic use [4]. PCAs are designed to deliver emission reductions by altering a population's economical behaviour, cognitive awareness, and social norms [2]. PCAs were once considered a policy measure ahead of their time.…”
Section: Personal Carbon Allowance -An Overviewmentioning
confidence: 99%
“…Introduction Research has shown that delivering on the goal set in the Paris agreement defining the 1.5-degree global temperature scenario may not be feasible with current measures [1,2]. To combat the worsening condition of the climate, the implementation of more stringent carbon management strategies on a large scale has been suggested [2]. One such proposed strategy is that of personal carbon allowances (PCA).…”
mentioning
confidence: 99%